Conception of an Independent Surveillance Authority in the Efforts to Protect Population Data - Daffa Ladro Kusworo; Andre Arya Pratama; Maghfira Nur Khaliza Fauzi; Maya Shafira (Fakultas Hukum Universitas Lampung, 2022)
The progress of digital transformation requires efforts to protect personal data as a guarantee of individual rights to overcome the large number of cases of data leakage and misuse, one of which is population data. The concretization of the government's efforts based on Article 28 G of the 1945 Constitution is realized through providing access to population data to all institutions, both state and private institutions for data verification. In addition, there is an obligation for data user parties to implement a Zero Data Sharing Policy with provisions prohibiting the dissemination or sharing of population data with third parties. However, various basic factors are influenced by the limited aspects of legal protection related to the class of personal data, and the authority between the data owner and the user, which makes it imperative to enact the current regulation on personal data protection. In addition, the establishment of an Independent Surveillance Authority is a must in ensuring the implementation of these regulations, because their duties and authorities are in line with the government's efforts in protecting population data. This study uses a normative legal research method with an approach to legislation and literature study, and uses descriptive analysis in managing qualitative data by applying a deductive method. The results of the study indicate that the need for legal guarantees must be accompanied by an element of optimal supervision through the establishment of an Independent Surveillance Authority in accordance with the standardization of the European Union General Data Protection Regulation (EU GDPR). Its independent position will prevent intervention from various parties for certain interests. Functionally, it is considered appropriate in optimizing the implementation of the Zero Data Sharing Policy through the conception of investigative authority and collective rights as a guarantee of human rights.